The health and welfare of dogs belonging to homeless people - David Leonard Williams; Sarah Hogg (Pet Behaviour Science, 2016)
A significant number of homeless people own dogs, with these animals contributing to the well-being of their owners by providing emotional support and in many cases, a reason for living as well as acting as what might be termed a social catalyst improving bonds between their owners. Yet many consider that homeless people should not be allowed, let alone encouraged to keep a dog. They consider that living with a homeless people must have a negative impact on the dog’s health and welfare compared to that of a dog owned by people with a home. Here we sought to determine the health and welfare of dogs owned by homeless people, comparing 50 dogs owned by homeless people with 50 owned by people living in a home. In contradistinction to the negative view noted above, we found that dogs owned by homeless people were healthy animals, less likely to be obese, had fewer behaviour issues such as aggression to strangers and separation anxiety when compared to dogs owned by people living in a conventional home. We suggest that these findings should be taken into account when deciding whether a homeless person with a dog should be allowed into a hostel, and indeed the general attitude of the public to homeless people living with a dog by their side on the street